Plasmonic Nanorattles as Next‐Generation Catalysts for Surface Plasmon Resonance‐Mediated Oxidations Promoted by Activated Oxygen. Issue 25 (9th May 2016) - da Silva, Anderson G. M.; Rodrigues, Thenner S.; Correia, Valquírio G.; Alves, Tiago V.; Alves, Rafael S.; Ando, Rômulo A.; Ornellas, Fernando R.; Wang, Jiale; Andrade, Leandro H.; Camargo, Pedro H. C.
Abstract: Nanorattles, comprised of a nanosphere inside a nanoshell, were employed as the next generation of plasmonic catalysts for oxidations promoted by activated O2 . After investigating how the presence of a nanosphere inside a nanoshell affected the electric‐field enhancements in the nanorattle relative to a nanoshell and a nanosphere, the SPR‐mediated oxidation of p ‐aminothiophenol (PATP) functionalized at their surface was investigated to benchmark how these different electric‐field intensities affected the performances of Au@AgAu nanorattles, AgAu nanoshells and Au nanoparticles having similar sizes. The high performance of the nanorattles enabled the visible‐light driven synthesis of azobenzene from aniline under ambient conditions. As the nanorattles allow the formation of electromagnetic hot spots without relying on the uncontrolled aggregation of nanostructures, it enables their application as catalysts in liquid phase under mild conditions using visible light as the main energy input. Abstract : Nanorattles : By taking advantage of the plasmon hybridization concept in Au@AgAu nanorattles, improved performances towards the surface plasmon resonance‐mediated oxidation of amines were achieved. As the nanorattle morphology makes possible the formation of electromagnetic hot spots, these materials are attractive next‐generation plasmonic catalysts for applications in liquid‐phase transformations under mild conditions.